Relation between Motivational Factors, Age, and Gender of Individuals Participating in a Swimming Project - Rodriguez Montero, Alejandro (2014)
The purpose of this study was to determine the relationship between motivational factors, sex and age on the participants at a project of swimming. The study included 107 subjects (71%) of the total of active participants in the project, of which 51 were men and 56 women, aged between 18 and 63 years (36,27 ± 10,67). The sample was divided into four age categories (18-29 years, 30-39 years, 40-49 years and 50 and over) and by sex. To know the reasons that lead people to engage physical exercise, self-report questionnaire Motives for the Practice of Physical Exercises (AMPEF), adapted by and Pintanel Niñerola Capdevila (2004) was applied. The results of the individual analysis showed that the factors: positive health and prevention; well-being and fun; muscular strength and endurance are important reasons for both men and women in all age categories, with values ≥ 7 (between 1 to 10). There were no significant differences in the total score between variables. The data reported are consistent with those reported in the literature. It is concluded that the main reasons for people to be physically active are: health, fun, well-being and improvement of physical, also found significant differences in the reasons relating to the challenge and competition between men and women, results also agree with previous publications.